Health-related quality of life among survivors in minority area 2 years after Jiuzhaigou earthquake: A cross-sectional study. Issue 10 (12th March 2021) - Zhang, Xi; Gao, Yuyang; Dai, Xuemei; Zhou, Jing; Yan, Liuqing; Hou, Furang; Yuan, Ping; Wen, Jin
Abstract : Abstract: To investigate the health-related quality of life (HRQoL) and related factors, the symptoms of posttraumatic stress disorder (PTSD) among earthquake survivors in minority area 2 years after Jiuzhaigou earthquake. Two years after the Jiuzhaigou earthquake, a cross-sectional survey was conducted by a multi-stage sampling approach. HRQoL was measured by the short form 12 (SF-12), PTSD was measured by the PTSD Check List-Civilian Version (PCL-C), and social support was measured by the Multidimensional Scale of Perceived Social Support. Descriptive statistics, t -tests, ANOVA and multiple linear regression analysis were used for data analysis. Of the 561 participants, the mean scores on the physical component summary (PCS) and mental component summary (MCS) were 46.36 ± 12.79 and 55.03 ± 8.73, and 5.73% reported the symptoms of PTSD. Lower PCS and MCS after an earthquake were associated with elderly age, physical illness, and low level of social support ( P < .05). Meanwhile, PTSD was significantly associated with MCS. These findings showed that physical disease and psychological symptoms can adversely affect the HRQoL of survivors. Moreover, providing higher social support to survivors should be considered as a way to improve the HRQoL outcomes of survivors.